Investigation the Properties of Ultra High Performance Concrete - Compressive Strength - HUSSEIN, KARAMA SAEED AL-JABERI (IRC, 2016)
Ultra-high performance concrete (UHPC) is one of a trending development technology in the concrete industry due to its high strength recorded. This strength is a combination of adequate aggregates, additives, cement and steel fibre, which provides a convincing evidence of greater strength. With an emerging technological development, there are critical problems and limitations associated with different kinds of concrete design structures. Therefore, this research aims to investigate the compressive strength of UHPC and provide a comparison amongst other conventional concrete structures. A new mechanical property to concrete structure is introduced when the fine aggregates are incorporated instead of coarse aggregates. I predicted UHPC‟s strength to be in the range of (120-150MPa), however, due to low quality materials and poor storage conditions during experimentation, the results have not reflected the predictions. The process and methods used is completed in four major stage: 1) the mixing, which combines nine different mix proportions to attain results, 2) casting, the fresh concrete is placed into cubes and cylindrical sizes, 3) curing, the concrete obtained into water tank at room temperature for a period of 7 -28 days, and 4) testing, for compressive strength of concrete. This allows a large number of data set to be recorded, hence, the results have been discussed.